1998
DOI: 10.1164/ajrccm.158.4.9710057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lung Volume Reduction Surgery on Gas Exchange and Pulmonary Hemodynamics at Rest and during Exercise

Abstract: Lung volume reduction surgery (LVRS) has become an extended surgery for emphysema in order to improve the dyspnea of severely affected patients. Because resection of lung areas may reduce the vascular bed, which is an important factor of pulmonary hypertension in emphysematous patients, especially during exercise, the aim of our study was to assess the outcome of pulmonary hemodynamics and gas exchange at rest and during exercise after LVRS. Nine patients had right heart catheterization before and 3 to 12 mo (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 28 publications
4
35
0
1
Order By: Relevance
“…LVRS may have adverse effects on pulmonary haemodynamics owing to the reduction of the vascular bed after the resection of lung tissue. Early studies have shown conflicting results, with increases in Ppa after LVRS in one study [130] but not in others [127,128]. A recent study as part of the National Emphysema Treatment Trial has shown no significant differences in terms of P pa and PVR, 6 months after medical treatment or LVRS [129].…”
Section: Lvrs and Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…LVRS may have adverse effects on pulmonary haemodynamics owing to the reduction of the vascular bed after the resection of lung tissue. Early studies have shown conflicting results, with increases in Ppa after LVRS in one study [130] but not in others [127,128]. A recent study as part of the National Emphysema Treatment Trial has shown no significant differences in terms of P pa and PVR, 6 months after medical treatment or LVRS [129].…”
Section: Lvrs and Lung Transplantationmentioning
confidence: 99%
“…There have been few studies on pulmonary haemodynamics before and after LVRS [127][128][129]. LVRS may have adverse effects on pulmonary haemodynamics owing to the reduction of the vascular bed after the resection of lung tissue.…”
Section: Lvrs and Lung Transplantationmentioning
confidence: 99%
“…OSWALD-MAMMOSSER et al [128] studied pulmonary haemodynamics in a group of patients with advanced COPD before and after LVRS. In their study resting Ppa remained unaltered after LVRS, whereas exercise Ppa decreased slightly, yet not significantly [128].…”
Section: Lung Volume Reduction Surgerymentioning
confidence: 99%
“…19 -24 However, most of the published reports are uncontrolled, unicenter trials involving small numbers of patients with short-term follow-up. 3,5,[17][18][19]22,23,[25][26][27] The National Emphysema Treatment Trial (NETT) represents the most extensively characterized patient cohort with severe emphysema undergoing repeated exercise testing. Here we report the effects of optimal medical therapy plus LVRS vs optimal medical therapy alone on maximum exercise after outpatient rehabilitation and through 2 years postrandomization to treatment.…”
mentioning
confidence: 99%